Campus journalism within your reach : a worktext for journalist wannabees in the campus - Bulusan, Ferdinand (Quezon City : Lorimar Publishing, Inc., 2016)
Preliminaries Copyright Foreword Preface Brief Book Reviews Dedication Table of Contents Unit 1 Linking Journalism and the Campus Paper Chapter 1 Foundational Concepts on Journalism Chapter 2The Campus Paper and the Publication Staff Unit II Journalistic Writing Skills Chapter 3The News: A Backgrounder Chapter 4Stairway to News Writing: Techniques and Principles Chapter 5 Getting Started: Crafting the Good Lead Chapter 6In Focus: Writing the Whole News Story Chapter 7Creativity Matters: Writing Features Articles Chapter 8Scuffle of Opinions: Writing Editorials Chapter 9 Personal Viewpoint: Writing Columns Unit III Ensuring Correctness and Consistency Chapter 10 Copy editing: Cleaning the Copy & Writing the Headline Chapter 11 Publication Style Guide: A Sample Bibliography Appendices Appendix A Philippine Press Institute The Philippine Journalists Code of Ethics Appendix B Republic Act No. 7079 An Act Providing for the Development and Promotion of Campus Journalism
Preliminaries Copyright Foreword Preface Brief Book Reviews Dedication Table of Contents Unit 1 Linking Journalism and the Campus Paper Chapter 1 Foundational Concepts on Journalism Chapter 2The Campus Paper and the Publication Staff Unit II Journalistic Writing Skills Chapter 3The News: A Backgrounder Chapter 4Stairway to News Writing: Techniques and Principles Chapter 5 Getting Started: Crafting the Good Lead Chapter 6In Focus: Writing the Whole News Story Chapter 7Creativity Matters: Writing Features Articles Chapter 8Scuffle of Opinions: Writing Editorials Chapter 9 Personal Viewpoint: Writing Columns Unit III Ensuring Correctness and Consistency Chapter 10 Copy editing: Cleaning the Copy & Writing the Headline Chapter 11 Publication Style Guide: A Sample Bibliography Appendices Appendix A Philippine Press Institute The Philippine Journalists Code of Ethics Appendix B Republic Act No. 7079 An Act Providing for the Development and Promotion of Campus Journalism
Includes bibliographical references.
300-399
Keywords: Journalism; Journalism, School